2019
DOI: 10.6001/biologija.v64i4.3904
|View full text |Cite
|
Sign up to set email alerts
|

“Floral-dip” transformation of Amaranthus caudatus L. and hybrids A. caudatus × A. paniculatus L.

Abstract: After “floral-dip” transformation of Amaranth plants with Agrobacterium tumefaciens strain GV3101 carrying pCBV19 gene vector that contained bar and gus genes, transgenic seeds were obtained. The functioning of the tran+sferred genes in Amaranthus tissues was confirmed with herbicide selection (PPT herbicide – phospinotricin) and gus gene activity. Positive results were obtained for cultivars “Karmin” and “Kremoviy rannii”. The percentage of GUS positive samples was 1% (for “Karmin”), 2.2% (for “Kremoviy ranni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(1 citation statement)
references
References 16 publications
0
1
0
Order By: Relevance
“…Meanwhile, surfactants can reduce the surface tension of target organs and act as attractants to increase the penetration of bacteria into plant tissues ( Curtis and Nam, 2001 ). Studies of floral dip transformation has been reported for Arabidopsis thaliana ( Bent, 2006 , Clough and Bent, 1998 , Narusaka et al, 2010 , Zhang et al, 2006 ), Raphanus sativus ( Curtis and Nam, 2001 ), Scherenkiella parvula ( Wang et al, 2019 ), Amaranthus caudatus L. ( Yaroshko et al, 2018 ) and Zea mays ( Guiqin et al, 2012 ). However, the transformation efficiency was<5%.…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, surfactants can reduce the surface tension of target organs and act as attractants to increase the penetration of bacteria into plant tissues ( Curtis and Nam, 2001 ). Studies of floral dip transformation has been reported for Arabidopsis thaliana ( Bent, 2006 , Clough and Bent, 1998 , Narusaka et al, 2010 , Zhang et al, 2006 ), Raphanus sativus ( Curtis and Nam, 2001 ), Scherenkiella parvula ( Wang et al, 2019 ), Amaranthus caudatus L. ( Yaroshko et al, 2018 ) and Zea mays ( Guiqin et al, 2012 ). However, the transformation efficiency was<5%.…”
Section: Introductionmentioning
confidence: 99%